Imaging of sports-related muscle and tendon injuries in children and adolescents - Vandervliet, E.; Vanhoenacker, F.; Snoeckx, A.; Gielen, J.; Van Dyck, P.; Parizel, P. (Medicine and Science in Tennis, 2008)
Sports-related muscle injuries are frequent in adults and youngsters. The presentation of muscle and tendon trauma largely depends on the patient`s age: in youngsters the skeleton is weaker than in adults, whereas their ligaments and tendons can withstand more force. Therefore, skeletal lesions, more specifically those of the physis, are common in children. The type of sports activity determines the nature of the lesion. Most commonly apophyses of the hip and pelvis are subject to avulsion fractures in youngsters, and in tennis the pelvis is the most likely site to be affected. Lesions can be either acute or chronic.